Iron stores at birth in a full-term normal birth weight birth cohort with a low level of inflammation. Issue 12 (23rd December 2020) - Zhang, Joy Y.; Wang, Jing; Lu, Qinsheng; Tan, Meizhen; Wei, Ru; Lash, Gendie E.
Abstract: Iron stores at birth are essential to meet iron needs during the first 4–6 months of life. The present study aimed to investigate iron stores in normal birth weight, healthy, term neonates. Umbilical cord blood samples were collected from apparently normal singleton vaginal deliveries ( n =854). Subjects were screened and excluded if C-reactive protein (CRP) > 5 mg/l or α1-acid glycoprotein (AGP) > 1 g/l, preterm (<37 complete weeks), term < 2500g or term > 4000g. In total, 762 samples were included in the study. Serum ferritin, soluble transferrin receptor (sTfR), hepcidin, and erythropoietin (EPO) were measured in umbilical cord blood samples; total body iron (TBI) (mg/kg) was calculated using sTfR and ferritin concentrations. A total of 19.8% newborns were iron deficient (ferritin 35 μg/l) and an additional 46.6% had insufficient iron stores (ferritin < 76 μg/l). There was a positive association between serum ferritin and sTfR, hepcidin, and EPO. Gestational age was positively associated with ferritin, sTfR, EPO, and hepcidin. In conclusion, we demonstrate a high prevalence of insufficient iron stores in a Chinese birth cohort. The value of cord sTfR and TBI in the assessment of iron status in the newborn is questionable, and reference ranges need to be established.